Rhetorical Persuasion Strategies in Presidential Campaigns: A Comparative Study in Two Countries - Paris, Atika Salman; Iskandar, Ifan; Dewanti, Ratna (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze and compare the rhetorical persuasion strategies in the presidential campaign speeches of Donald Trump in the United States and Prabowo Subianto in Indonesia. The approach employed is descriptive qualitative, using a comparative case study design. Data were collected from the official speech transcripts of both candidates and analyzed through classical rhetorical categories, ethos, pathos, and logos, complemented by framing analysis, agenda-setting, and critical discourse analysis. Findings reveal that Donald Trump employed a confrontational and populist rhetorical strategy. He constructed an image of himself as the people's protector against the political elite, evoked collective emotions such as fear and anger, and used hyperbolic logic to reinforce his political arguments. His rhetorical style was dominated by metaphors of battle and national crisis. In contrast, Prabowo Subianto employed a more nationalistic and integrative rhetorical style. He built credibility through narratives of nationalism, conveyed messages of hope and unity, and promoted a development and self-reliance agenda as the logical framework of his campaign. The analysis indicates that campaign speeches are not merely tools of political communication but also practices of meaning-making that reflect power structures, political identities, and issue priorities. This study offers a deeper understanding of the dynamics of political rhetoric within different cultural contexts and contributes to the development of cross-national political communication studies.